Caffeine Inhibits Choroidal Neovascularization Through Mitigation of Inflammatory and Angiogenesis Activities - Sorenson, Christine M.; Song, Yong-Seok; Zaitoun, Ismail S.; Wang, Shoujian; Hanna, Barbara A.; Darjatmoko, Soesiawati R.; Gurel, Zafer; Fisk, Debra L.; McDowell, Colleen M.; McAdams, Ryan M.; Sheibani, Nader (Frontiers in Cell and Developmental Biology, 2021)
Adenosine receptors (AR) are widely expressed in a variety of tissues including the retina and brain. They are involved in adenosine mediated immune responses underlying the onset and progression of neurodegenerative diseases. The expression of AR has been previously demonstrated in some retinal cells including endothelial cells and retinal pigment epithelial cells, but their expression in the choroid and choroidal cells remains unknown. Caffeine is a widely consumed AR antagonist that can influence inflammation and vascular cell function. It has established roles in the treatment of neonatal sleep apnea, acute migraine, and post lumbar puncture headache as well as the neurodegenerative diseases such as Parkinson and Alzheimer. More recently, AR antagonism with caffeine has been shown to protect preterm infants from ischemic retinopathy and retinal neovascularization. However, whether caffeine impacts the development and progression of ocular age-related diseases including neovascular age-related macular degermation remains unknown. Here we examined the expression of AR in retinal and choroidal tissues and cells. We showed that antagonism of AR with caffeine or istradefylline decreased sprouting of thoracic aorta and choroid/retinal pigment epithelium explants in ex vivo cultures, consistent with caffeine’s ability to inhibit endothelial cell migration in culture. In vivo studies also demonstrated the efficacy of caffeine in inhibition of choroidal neovascularization and mononuclear phagocyte recruitment to the laser lesion sites. Istradefylline, a specific AR 2A antagonist, also decreased choroidal neovascularization. Collectively, our studies demonstrate an important role for expression of AR in the choroid whose antagonism mitigate choroidal inflammatory and angiogenesis activities.